2012
DOI: 10.1016/j.apcatb.2012.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of precursor on the performance of alumina for the dehydration of methanol to dimethyl ether

Abstract: Highlights Effect of precursors on the catalytic performance of alumina. AN samples is higher activity than AC, while AN550 is the optimum one. The AN550 showed methanol conversion and DME selectivity of 72% and 100% at 250 °C, respectively. Acid site density affected catalytic performance among the catalysts with alumina phase. Synthesis of alumina catalyst with high activity compared to commercial γ-Al 2 O 3 .Page 3 of 33 A c c e p t e d M a n u s c r i p t Abstract Dimethyl ether (DME) is amongst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
107
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 38 publications
6
107
0
Order By: Relevance
“…The preparation of alumina has been described elsewhere [10]. It was prepared from aluminium nitrate nonahydrate that was then precipitated by ammonia solution giving a precipitate which dried at 120 °C and designated as AN120, followed by calcination at 550 °C and designated as η-Al 2 O 3 .…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…The preparation of alumina has been described elsewhere [10]. It was prepared from aluminium nitrate nonahydrate that was then precipitated by ammonia solution giving a precipitate which dried at 120 °C and designated as AN120, followed by calcination at 550 °C and designated as η-Al 2 O 3 .…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…Methanol dehydration is known to take place on Lewis acid-pair sites and its rate increases as the surface Lewis acidity increases [11]. It was well reported that γ-Al 2 O 3 , a typical Lewis acid catalyst and also the η-Al 2 O 3 used in the study, can catalyse dehydration of MTD [10]. Several reaction mechanisms have been presented for methanol dehydration on acid catalysts [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations